What influences women’s participation in water governance? Learning from polder zones of Bangladesh - Singaraju, Niyati; Sarker, Mou Rani; Akter, Rima; Das, Mohanambrota; Batas, Mary Ann; Mondal, Manoranjan K.; Puskur, Ranjitha; Yadav, Sudhir (Informa UK Limited, 2025)
Coastal regions of Bangladesh face severe climate-related water challenges, with disproportionate impacts on women due to entrenched gender inequalities in access to resources, mobility, and decision-making. This study examines the extent and quality of women’s participation in Water Management Groups (WMGs) across four coastal polders using a mixed-methods approach. Quantitative findings show that women’s membership is shaped by social norms, domestic roles, institutional dynamics, and access to resources, while men’s is driven mainly by production benefits. Moreover, women’s membership is further influenced by their social identity. Gender quotas have improved women’s formal representation, but decision-making within WMGs remains male-dominated, particularly in water infrastructure and financial planning. Qualitative insights highlight that restrictive social norms and intra-household power dynamics often render women’s participation symbolic. Leadership positions are still held overwhelmingly by men. Over 80% of women reported that membership improved their access to information and enhanced their recognition and voice in household decision-making. Yet, meaningful engagement remains limited without targeted efforts to challenge the structural and normative constraints that shape gendered exclusions. The study calls for gender-transformative approaches to water governance that move beyond quotas to strengthen women’s agency, voice, and leadership in water resource management.